Executive time utilization in the Philippine provincial governorship - Walsh, Thomas P. (1976)
Philippine provincial governors are subject to diverse and demanding but uncodified role expectations of their constituents. Not all of these expectations, however, can be met. On the basis of those that can be met, the study makes inferences about gubernatorial perceptions of role priorities and responsibilities. Governors are preoccupied more with ceremonial public relations or pakikisama roles than with policy and executive leadership. A governor's "average" day is taken up by almost unending- streams of callers on a variety of missions, visits to barrio projects, fiestas, baptismals, etc., and snatches of paperwork in the office. Moreover, most governors must spend 20% or more of their tenure traveling to
Manila on follow-up-and-facilitate missions. These preoccupations may run counter to their view of what their roles should be, but most governors are unable or unwilling to challenge the prevailing structure of popular expectations.
Keywords: Governors -- Powers and duties; Public administration -- Research; Local government